Bone scintigraphy in the diagnosis of transthyretin amyloidosis: a different performance in Portuguese hereditary variant?. (14th October 2021) - Dias De Frias, A F; Rodrigues, P; Costa, R; Campinas, A; Pereira, A; Alexandre, A; Hipolito Reis, A; Torres, S
Abstract: Introduction: Bone scintigraphy using radioactive technetium-99m and 3, 3-diphosphono-1, 2-propanodicarboxylic acid (DPD) has been increasingly used to diagnose myocardial involvement of mutated or wild-type transthyretin amyloidosis (ATTR). However, most studies that proved a high sensitivity and specificity of the technique were not in patients with the "Portuguese variant" (Val30Met) mutation in transthyretin (TTR). Other authors had already suggested that in these patients the DPD scan could be less accurate. Methods: Observational study of patients referred to Cardiology clinic with suspicion of ATTR cardiomyopathy. We only included patients with data from echocardiogram and DPD scan. For statistical analyses, SPSS was used, p<0.05 for statistical significance. Logistic regressions were used to test an association between DPD result and different covariates. Results: Of 273 patients referred with suspicion of cardiac ATTR, we studied 97 patients that did an echocardiogram and a DPD scan. Among the 75 cases with mutated TTR (Val30Met), median age was 36 (IQR 34) and 60% were males. 60 had increased ventricular wall thickness (IVWT) >12 mm, but only 24 had a positive DPD (defined as a visual score >2). Even though a higher wall thickness was associated with a positive DPD (p=0.004), 18 patients with a negative scan had IVWT >14 mm. The DPD results was significantly associated with prior liver transplantation (LT) – p<0.001; 95% CI (7.1; 503.6) – and age at first symptoms – p<0.001; 95% CI (1.036; 1.113); 66.7±10.5 versus 34.8±10.2 years-old for those with and without a positive scan, respectively. Interestingly, fewer patients with a positive scan had neurologic symptoms (74% versus 96%, p=0.009), ophthalmologic, urologic or renal involvement, even though creatinine clearance was on average lower (p=0.01). We did not find a significant association between DPD result and sex, conduction disorders, NT-proBNP, troponin T or treatment with tafamidis. Patients on tafamidis had on average lower IVWT, independent of age (median of 13 versus 14 mm; p=0.020). 4 patients with negative DPD did an endomyocardial biopsy, that was positive for amyloid in 3 cases. In comparison, in the 22 cases with wild-type TTR, there were significantly more males (86%) and patients were older (median age was 81 (IQR 9)). All patients had IVWT (that was significantly higher than in mutated ATTR) and DPD scan was negative in only 2 patients (that had a visual score of 1). Systolic dysfunction was significantly more frequent (59% versus 8%). The occurrence of death or hospitalization for heart failure was significantly higher. Conclusions: DPD-scintigraphy seems more sensitive in patients with late onset mutated ATTR or with wild-type ATTR. It is less accurate in early onset patients with Val30Met mutation and particularly if they underwent LT. In those patients, further investigation is needed before excluding myocardial involvement. FUNDunding Acknowledgement: Type of funding sources: None.